Arbuscular Mycorrhizal Fungi and Glomalin-Related Soil Protein as Potential Indicators of Soil Quality in a Recuperation Gradient of the Atlantic Forest in Brazil - Vasconcellos R.L.F. (2016)
© 2016 John Wiley & Sons, Ltd.This study aimed at surveying arbuscular mycorrhizal fungi (AMF) species and glomalin-related soil protein (GRSP) to understand their role as presumable biological indicators of soil quality in an undisturbed forest site (NT) and three sites with different management histories, soil textures, and different ages of recovery after reforestation for 20 (R20), 10 (R10) and 5years (R05). Our objective was to determine how physical, chemical and microbiological soil attributes influence AMF species distribution, total-GRSP (T-GRSP) and easily extractable-GRSP (EE-GRSP). Glomus and Acaulospora were related to impacted sites, Gigaspora rosea to sites R10 and R20 that have different management histories and soil textures and Glomus geosporum to sites NT and R10, suggesting some influence of texture on its distribution. Scutellospora pellucida and other species were found only in one season. Correlations between EE-GRSP and T-GRSP on the one hand and total carbon and nitrogen, dehydrogenase and urease activity, microbial biomass carbon and microbial biomass nitrogen, on the other, reached values of 40-70% and were especially strong in summer. Soil bulk density had a negative and macroporosity a positive effect only on EE-GRSP, suggesting the necessity to choose either EE-GRSP or T-GRSP as biological indicator depending on the soil characteristics and management. This study demonstrates the effect of recovery age, seasonality and other soil attributes on AMF and GRSP distribution and shows that these biological attributes may be used as indicators of soil quality in the Atlantic forest in Brazil.